Training as an institutional configuration and articulation factor. The (bad?) example of the Public Prosecutor - Crespo Barquero, Pedro José (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
A solid legal education is the essential basis for the correct performance of any Law related profession. But when this professional activity is carried out at the service of an institution, training can also constitute a fundamental tool for the organization and improvement of the public service that institution provides, in terms of quality and efficiency. The Spanish Public Prosecutor's Office offers a magnificent example..., which for now has not been possible.
Keywords: Training; institutions; organization; public service; quality; efficiency; public prosecutor's office